Musculoskeletal discomforts among young nurses: A foreshadowing and the reasons behind - Chowdhury, Upasana; Das, Tamal; Gangopadhyay, Somnath (International Journal of Occupational Safety and Health, 2026)
Introduction: Musculoskeletal discomfort in nurses is becoming more common. Studies have revealed that age and exposure to causative factors over the years might trigger symptoms. The goal of this study was to evaluate the prevalence and factors influencing the work-related musculoskeletal discomfort indications among young female nurses.Methods: This cross-sectional study was performed between August, 2020 to November 2022. Maintaining the inclusion and exclusion criteria of this study, female registered nurses were chosen with an age limit of 29 years. Modified Nordic Questionnaire, Physical Activity Level (PAL) questionnaire, Copenhagen Psychosocial Questionnaire (COPSOQ), and Rapid Entire Body Assessment (REBA) tool were used. Percentage analysis, Correlation analysis, and Binary Logistic Regression tests were performed.Results: 79.4% of participants reported the presence of musculoskeletal discomfort in at least one body region, and the most frequent among them was lower back pain (LBP) with a percentage of 51.4%. Quantitative Demand, General Health, and Vitality displayed a significant relation with LBP. Posture analysis exhibited high bending angles.Conclusion: Musculoskeletal discomfort complaints among young nurses disclosed an alarming prevalence. High work demand and frequently unfavorable postures aided the outcomes. Addressing the discomfort among young workers is of the utmost priority to ensure good health and forestall deteriorating symptoms in the future. Amelioration of work-related discomforts can lead to improved performance, enhanced job quality, and improved physical and mental health. As health sectors play a vital role in society and embrace a large number of young workers, assessing the workers' discomfort leads to a better and flourishing tomorrow led by healthier individuals.